تعدد دلالة المصطلحات الصوتية حتى نهاية القرن الرابع الهجري: The significance of phonemic terms until the end of the fourth century AH - Habib, Ahmed Khayel (SIBAWAYH Arabic Language and Education, 2021)
تضمن هذا البحث دراسة ثلاثة محاور: (المخرج، الهمز والنبر، الجهر والهمس)، وسبب كتابة هذا البحث أن بعضاً من الباحثين والدراسين قد خلط بين مفاهيم هذه المصطلحات الصوتية نتيجة تداخلها وتعددها؛ فضلاً عن اضطراب فهمهم لماهية كل واحد منها، وسيكون تركيز الجهد منصباً على ما ذكره علماء الأصوات من اللغوين القدامى، إذ إن كل مصطلحٍ يدل على معنى ربما يتداخل مع مصطلح لمفهوم اخر؛ وقد اعتمدت في تحديد مفهوم المصطلحات وما يرادفها على التفكير الصوتي عند علمائنا الأوائل كالخليل، وسيبويه، وابن جني، وابن سينا وغيرهم. Multiplicity of phonemic terms until the end of the fourth century AH" This paper included three paragraphs، which are as follows: (Director. Humming. Accent. Speaking and whispering). That is because many researchers and scholars have confused the concepts of these phonemic terms as a result of interference and multiplicity، as well as the understanding that reached and from the ancient linguists، as each term indicates a meaning that may overlap with another term and concept، and the focus was on the early scholars، especially Hebron Sibawayh, Ibn Jinni, Ibn Sina and other. Keywords: Terminology, Acoustic, Century